(3cJGH GdehGYX GdHGdZIs - (3GdgeOGfj GdcGXej, , EeGe GdMQejf, eMeO Hf YHO GdhgGH Hf OGhO, J(B1305(3g`s ((3eMeO GdMSjf GdfLa BHGOjs)
(3ChdgG (B:s
(3GdMeO ddg Pj Gdeff hGdBdGA GdSGHZI(B...(3Ef GdehGYX CYXe eG jLdh UOC GdbdhH hCLd eG jUbd Yf GdCaFOI(B...s
(3BNQgG (B:s
...(3hdg Ydjg GdSdGe aj cd efRd ef gPg GdefGRd eUGFH haVGFd(B...(3hdjcf gPG BNQ eG fedjg aj GdLRA GdChd(B...s
(3aQZ efg eDdag SfI (B1293(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B473s
(3GdPQjYI(B:(3L(B23(3,U(B140(3,Qbe(B8733s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs